Effect of copper nanoparticles and copper ions on the architecture of rainbow trout olfactory mucosa - Parastoo Razmara (Elsevier, 2021)
Olfactory epithelial cells are in direct contact with myriad environmental contaminants which may consequently disrupt their structure and function. Copper ions (Cu2+) and copper nanoparticles (CuNPs) are two types of olfactory neurotoxicants. However, their effects on the structure of olfactory epithelium are largely uninvestigated. The density of olfactory goblet cells in CuNP- and Cu2+ - exposed rainbow trout was assessed using light microscopy throughout time. In both copper (Cu) treatments, the number of goblet cells increased initially over the 24 h exposure and then recovered to normal throughout the 96 h exposure. These data suggested the 96 h exposure to Cu contaminants interfered with protective barrier provided by goblet cells. Nonetheless, lamellar and epithelial thickness of olfactory rosette did not change in the Cu-exposed fish. The gene transcript profile of olfactory mucosa studied by RNA-seq indicated Cu2+ and CuNPs differentially targeted the molecular composition of cell junctions. In the Cu2+ treatment, reduced mRNA abundances of tight junctions, adherens junction, desmosomes and hemidesmosomes, suggest that Cu2+-exposed olfactory mucosal cells had weak junctional complexes. In the CuNP treatment, on the other hand, the transcript abundances of cell junction compositions, except adherens junction, were upregulated. Transcripts associated with gap junctional channels were increased in both Cu treatments. The elevated transcript levels of gap junctions in both Cu treatments suggested that the demand for intercellular communication was increased in the Cu-exposed olfactory mucosa. Overall, our findings suggested that Cu2+ induced greater adverse effects on the molecular composition of olfactory cell junctions relative to CuNPs. Impairment of junctional complexes may disrupt the structural integrity of olfactory mucosa.